HUBUNGAN PENGETAHUAN DAN SIKAP PERAWAT TERHADAP PEMBUANGAN SAMPAH MEDIS DI RUMAH SAKIT UMUM DAERAH TENGKU MANSYUR KOTA TANJUNG BALAI TAHUN 2018 - NOVA LUMINDA SARI; ROSTINA AFRIDA POHAN (LP2MTBM MAKARIOZ, 2019)
Infectious medical waste is a hazardous material that must be managed properly so as not to be a source of new infectious for people around the hospital as well as for health workers in the hospital itself. Hospital operations produce various kinds of waste in the form of liquid, solid and gas. The purpose of this study was to determine the relationship of knowledge and attitude of nurses to medical waste disposal at the General Hospital of the City Padangsidimpuan 2016. This study was descriptive correlative study. The population in this study is the general hospital nurse Padangsidimpuan city as many as 84 people. The results of the majority of the 84 respondents have a high knowledge category as many as 44 people (52.4%). The attitude of the majority of the 84 respondents had a negative category as many as 47 people (56.0%). Relationships level of knowledge of nurses to medical waste disposal at the General Hospital of the City Padangsidimpuan 2016, according to the results of Chi-Square test results obtained p-value of 0.023. Relationships level nurses attitude towards the disposal of medical waste in the General Hospital of the City Padangsidimpuan 2016, according to the results of Chi-Square test results obtained p-value of 0.014.